Indonesian Capital Market Response to U.S. Federal Funds Rate Increase Announcements - Maharani, Ketut Bintang; Asmara Putra, I Nyoman Wijana; Anggara, I Wayan Gde Wahyu Purna (E-Jurnal Akuntansi; Vol 34 No 6 (2024)DO - 10.24843/EJA.2024.v34.i06.p20, 2024)
This research aims to examine whether there are abnormal returns due to the increase in the Federal Funds Rate (FFR) in the United States on February 1, 2023, March 24, 2023, May 3, 2023, and July 26, 2023. The observation period for this study spanned two days before and after each event, with a sample size of 250 companies obtained using the Cochran formula. The sampling method employed was simple random sampling. The data analysis technique utilized was the one-sample Wilcoxon signed-rank test. The results of the analysis indicate that of the four FFR increase events, only the event on March 24, 2023, resulted in a significant abnormal return. It was concluded that this FFR increase event had an impact. This significant abnormal return was predicted to be due to the normalization of policies on the Indonesian Stock Exchange, which occurred one day before the event (t-1) of the FFR increase on March 24, 2023. Keywords: Abnormal Return; Event Study; Fed Funds Rate